ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DAN KECERDASAN EMOSIONAL SISWA TERHADAP HASIL BELAJAR SISWA - Sihite, Epiphanias Br; Pangaribuan, Firman; Tambunan, Hardi (Universitas Quality, 2024)
The aim of this research is to determine the level of students' mathematical communication skills and emotional intelligence on student learning outcomes in mathematics learning. This research uses a quantitative type of research with one independent variable, namely emotional intelligence and one dependent variable, namely mathematics learning outcomes. The sampling technique in this research used purposive sampling so that the sample used was 60 students from class VI of SD Cenderamata. Data collection was carried out by means of literature study, distribution of emotional intelligence questionnaires and odd midterm exam (UTS) score data for the 2023/2024 academic year. Based on these data, it can be concluded that class VI students at Cenderamata Elementary School have relatively moderate emotional intelligence, meaning that the students' emotional intelligence is good. This is reinforced by the relationship between emotional intelligence and mathematics learning outcomes and that 17.24% of students' mathematical communication skills are in the high category with a frequency of 10 students, 70.69% are in the medium category with a frequency of 42 students and 12, 07% of students are in the low category with a frequency of 8 students. Based on these data, it can be concluded that class VI students at Cenderamata Elementary School have low mathematical communication skills. From the results it can be interpreted that there is a moderate relationship between communication skills and emotional intelligence on mathematics learning outcomes with the contribution of emotional intelligence to the high and low levels of mathematics learning outcomes of 31.6% and 68.4% were influenced by other factors outside the research.